The paradoxical strength of primary healthcare and the course of the National Health System - González López-Valcarcel, Beatriz (Revista Española de Comunicación en Salud, 2025)
Health systems based on strong primary care are superior because they achieve more health at lower cost and with equity. Primary care in Spain has generally good indicators, but young physicians shy away from family medicine in primary care and there is a dissociation between private and social values: what is socially necessary is not individually attractive to many professionals. In recent years there have been multiple plans and strategies, at international, state and regional levels, to “save” primary care, and an intense debate, tinged with interests, in which the labor demands of workers are sometimes identified with social welfare. The main idea of the organizational changes is that every minute of professional contributes value, and that each professional works at the limit of his or her competencies. Some clear and exemplary signals can be very effective, such as improving economic and working conditions in primary care, the greater presence of family medicine in universities and the encouragement of research in primary care. The generational renewal of family physicians and the potential of digitalization to consolidate networks where rural professionals do not feel isolated are reasons for optimism.